Non-competitive AMPA glutamate receptors antagonism by perampanel as a strategy to counteract hippocampal hyper-excitability and cognitive deficits in cerebral amyloidosis. (1st March 2023) - Bellingacci, Laura; Tallarico, Martina; Mancini, Andrea; Megaro, Alfredo; De Caro, Carmen; Citraro, Rita; De Sarro, Giovambattista; Tozzi, Alessandro; Di Filippo, Massimiliano; Sciaccaluga, Miriam; Russo, Emilio; Leo, Antonio; et al.
Abstract: Pathological accumulation of Aβ oligomers has been linked to neuronal networks hyperexcitability, potentially underpinned by glutamatergic AMPA receptors (AMPARs) dysfunction. We aimed to investigate whether the non-competitive block of AMPARs was able to counteract the alteration of hippocampal epileptic threshold, and of synaptic plasticity linked to Aβ oligomers accumulation, being this glutamate receptor a valuable specific therapeutic target. In this work, we showed that the non-competitive AMPARs antagonist perampanel (PER) which, per se, did not affect physiological synaptic transmission, was able to counteract Aβ-induced hyperexcitability. Moreover, AMPAR antagonism was able to counteract Aβ-induced hippocampal LTP impairment and hippocampal-based cognitive deficits in Aβ oligomers-injected mice, while retaining antiseizure efficacy. Beside this, AMPAR antagonism was also able to reduce the increased expression of proinflammatory cytokines in this mice model, also suggesting the presence of an anti-inflammatory activity. Thus, targeting AMPARs might be a valuable strategy to reduce both hippocampal networks hyperexcitability and synaptic plasticity deficits induced by Aβ oligomers accumulation. Highlights: AMPAR modulation by PER reduces neuronal hyperactivity and synchronization. AMPAR modulation ameliorates cognitive functions and performances in Aβ mice models. PER reduces the levels of pro-inflammatory cytokines in Aβ oligomers-injected mice.